Risk factors of CMV infection in patients after umbilical cord blood transplantation: a multicenter study in China - Tong, Juan; Sun, Zimin; Liu, Huilan; Geng, Liangquan; Zheng, Changcheng; Tang, Baolin; Song, Kaidi; Yao, Wen; Liu, Xin (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
Objective: This retrospective study examined risk factors for cytomegalovirus (CMV) infection after umbilical cord blood transplantation (UCBT) and the impact of CMV infection on patient survival. Methods: In all 176 patients, plasma CMV DNA was negative prior to the transplantation, and examined twice a week for 100 d, and then once weekly for additional 300 d. Preemptive antiviral therapy (ganciclovir or foscarnet) was started in patients with >1,000/mL copies of CMV DNA but no full-blown CMV disease, and was discontinued upon two consecutive negative reports of blood CMV DNA test. The survival and risk factors for CMV infection or disease were examined using logistic regression. Results: CMV infection developed in 71% (125/176) of the patients, with a median onset of 32 d. Four patients (2.3%) developed CMV disease. Neither the 5-year overall survival (OS) nor event-free survival (EFS) differed significantly in infected patients vs. those with no infection (59.4% vs. 64.8%, P=0.194; 53.4% vs. 59.1%, P=0.226). A stepwise multivariate analysis indicated an association of CMV infection with age, high-dose glucocorticoids, the number of transplanted CD34+ cells, and the number of platelet transfusion, but not with gender, the conditioning regimen, and the day of neutrophil recovery and chronic graft-versus-host disease (cGVHD). Conclusions: CMV infection is very common after UCBT, but does not seem to affect long-term survival with preemptive antiviral treatment.